Cobalt-Porphyrin-Platinum-Functionalized Reduced Graphene Oxide Hybrid Nanostructures: A Novel Peroxidase Mimetic System For Improved Electrochemical Immunoassay - Jian Shu; Zhenli Qiu; Qiao‐Hua Wei; Junyang Zhuang; Dianping Tang (2015)
Abstract 5,10,15,20-Tetraphenyl-21H,23H-porphine cobalt flat stacking on the reduced graphene oxide with platinum nanoparticles (PtNPs/CoTPP/rGO) were first synthesized and functionalized with monoclonal rabbit anti-aflatoxin B 1 antibody (anti-AFB 1 ) for highly efficient electrochemical immunoassay of aflatoxin B 1 (AFB 1 ) in this work. Transmission electron microscopy (TEM), atomic force microscope (AFM) and spectral techniques were employed to characterize the PtNPs/CoTPP/rGO hybrids. Using anti-AFB 1 -conjugated PtNPs/CoTPP/rGO as the signal-transduction tag, a novel non-enzymatic electrochemical immunosensing system was designed for detection of target AFB 1 on the AFB 1 -bovine serum albumin-functionalized sensing interface. Experimental results revealed that the designed immunoassay could exhibit good electrochemical responses for target analyte and allowed the detection of AFB 1 at a concentration as low as 5.0 pg mL −1 (5.0 ppt). Intra- and inter-assay coefficients of variation were below 10%. Importantly, the methodology was further validated for analyzing naturally contaminated or spiked blank peanut samples with consistent results obtained by AFB 1 ELISA kit, thus providing a promising approach for quantitative monitoring of organic pollutants.